Attitudes of ophthalmology and pediatrics residents toward professionalism - Marzieh Najjaran; Mohammad Etezad Razavi; Javad Heravian Shandiz; Hamed Tabesh; Ali Emadzadeh (Mashhad University of Medical Sciences, 2021)
Background: Professionalism is an important competency for residents in medical education. The present study aimed to assess the attitudes of ophthalmology and pediatrics residents toward professionalism.Methods: In this cross-sectional study, the Persian version of the modified American Board of Internal Medicine (ABIM) questionnaire was distributed among all the ophthalmology and pediatrics residents in Mashhad University of Medical sciences, during the academic year of 2018-2019. The questionnaire consists of demographic data and 15 items covering three domains including excellence, honor/integrity and altruism/respect.Results: Out of 103 residents, 77 (74.75%) respondents completed the questionnaires. The overall mean scores of professionalism were reported as 107.60±15.5 and 105.64±10.8 (out of 150) for the ophthalmology and pediatrics residents, respectively, and there was no significant difference between the two groups in this regard (P=0.53). The mean values for items forming the excellence domain were 5.44±1.8 and 5.47±1.4 (out of 10) for the ophthalmology and pediatrics residents, respectively (P=0.93). The mean values for the honor/integrity domain were reported as 8.38±1.2 and 8.2±1 (out of 10) for the ophthalmology and pediatrics residents, respectively (P=0.17). Regarding the altruism/respect domain, the mean scores were 7.46±1.1 and 7.37±0.7 (out of 10) for the ophthalmology and pediatrics residents, respectively (P=0.68).Conclusion: The results of the current study revealed a moderate level of attitudes toward professionalism among the ophthalmology and pediatrics residents. The importance of giving more attention to the excellence domain seems a priority for the development of professionalism in residency programs.